Results of sainfoin breeding in the Stavropol Territory - N. S. Lebedeva; V. V. Chumakova; S. A. Sukharev (Зерновое хозяйство России, 2022)
Modern Agricultural production is characterized by an increased need for specialized, highly productive, complementary varieties of feed crops adapted to specific natural and climatic conditions, grown using various technologies, for certain groups of animals. Among the perennial legumes in the south of Russia, sainfoin is in special demand. The purpose of the current study was to estimate the variety samples of various types of sainfoin and a new variety of Transcaucasian sainfoin ‘Kravtsov’ according to the main economically valuable traits and properties when used for feed and seeds. The study was carried out in the zone of unstable moisture in the Stavropol Territory. The soil of the experimental field was represented by low-humus micellar-carbonate medium loamy chernozem, with 3.2 % humus, 12 mg/kg phosphorus and 260 mg/kg potassium in the arable layer. The prevailing weather conditions during the research period made it possible to give a comprehensive estimation of the studied material. According to the results of Competitive Variety Testing, a variety sample of Transcaucasian sainfoin was selected from the studied three types of the crop, which, due to the results of the State Variety Testing in 2021, was included in the State List of Breeding Achievements of the Russian Federation with permission to use in all regions of the country. A new variety of Transcaucasian sainfoin ‘Kravtsov’ has a complex of such economically valuable traits as intensive spring and post-harvest regrowth, high foliage (42–45 % in the first cut, 52–57 % in the second cut), and resistance to unfavorable environmental factors. The plant height in the budding phase was 110–115 cm, which exceeded standard plants’ height by 10–15 %. The variety is highly resistant to drought and lodging, tolerant to diseases and pests. The variety is highly productive with 33.8 t/ha of green mass, 9.7 t/ha of hay and 1.1 t/ha of seeds. There is 17% crude protein in dry matter. 1000-seed weight is 23–25 g.